THE ROLE OF SHADOWING TECHNIQUE IN IMPROVING LISTENING SKILLS OF LANGUAGE LEARNERS - Anorboyeva Nozima Ibodullayevna (Лучшие интеллектуальные исследования, 2023)
Annotation. Since, there are a lot of different methods and learning techniques for learning new languages efficiently such as shadowing method. And in this science work, the information is provided by similarities and differences, cons and pros between other techniques and this shadowing method.